2013
DOI: 10.3389/fnhum.2013.00450
|View full text |Cite
|
Sign up to set email alerts
|

Three Ways in Which Midline Regions Contribute to Self-Evaluation

Abstract: An integration of existing research and newly conducted psychophysiological interaction (PPI) connectivity analyses suggest a new framework for understanding the contribution of midline regions to social cognition. Recent meta-analyses suggest that there are no midline regions that are exclusively associated with self-processing. Whereas medial prefrontal cortex (MPFC) is broadly modulated by self-processing, subdivisions within MPFC are differentially modulated by the evaluation of close others (ventral MPFC:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 79 publications
2
61
0
Order By: Relevance
“…The present study particularly focused on these two seed regions among various CMS regions, because of following regions: first, these regions showed significant activity under moral task conditions in the previous neuroimaging studies [39,40] as well as the present study; second, these regions are associated with self-evaluation [62,93] and particularly autobiographical memory processing [36,37] that constitute the basis of the moral belief system, moral identity, and finally moral self [33]. These seed regions were selected based on the peak voxel coordinate information as the result of the whole-brain voxelwise t-tests (described above) and the brain atlas obtained by previous functional connectivity studies [94,95].…”
Section: Image Data Analysismentioning
confidence: 84%
See 3 more Smart Citations
“…The present study particularly focused on these two seed regions among various CMS regions, because of following regions: first, these regions showed significant activity under moral task conditions in the previous neuroimaging studies [39,40] as well as the present study; second, these regions are associated with self-evaluation [62,93] and particularly autobiographical memory processing [36,37] that constitute the basis of the moral belief system, moral identity, and finally moral self [33]. These seed regions were selected based on the peak voxel coordinate information as the result of the whole-brain voxelwise t-tests (described above) and the brain atlas obtained by previous functional connectivity studies [94,95].…”
Section: Image Data Analysismentioning
confidence: 84%
“…The CMS regions particularly the MPFC and PCC selected in the present study and constitute the cortical midline structures, which significantly influenced insula regions, are regarded to be the loci of selfhood, or at least the autobiographical processing that is deemed to be the core selfhood-related process associated with moral functioning in case of the PCC [36,37], at the neural level (Damasio, 2010;Northoff and Bermpohl, 2004). Previous neuropsychological studies have demonstrated that the activity in the MPFC region as a part of the CMS are closely associated with self-evaluation of a belief system and morality [29,42,62,93,135,136]; even socio-moral emotions are also modulated by this self-evaluative mechanism [137]. Furthermore, the PCC region is associated with other important self-related processes, particularly self-referencing and autobiographical memory processing [33,[66][67][68][69]; although some recent studies have shown that this region might not be associated with selfhood-related processes in general, it is closely associated with the autobiographical memory processing [36,37].…”
Section: Granger Causality Between Cms and Insula Regionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCC, as part of the DMN, is also discussed, along with mirror neurons, by Molnar-Szakacs and Uddin (2013) in their discussion of the role of CMS in self-relevant and social processing, suggesting a key role for them in embodiment and simulation. Also considering the role of midline regions in social cognition, Flagan and Beer (2013) discuss the mPFC and the social self, describing how different sub-regions may be involved in different aspects of self-evaluation.Alterations of self are seen in many mental disorders, as well as in disorders of consciousness (DOC) -the focus of the third group. Crone et al (2013) present an fMRI study of the response to self/other names in CMS of patients with DOC, adding to the literature on self in such conditions, as reviewed here by Demertzi et al (2013).…”
mentioning
confidence: 99%